Effect of Changing Gloves Before Placental Extraction on Incidence of Postcesarean Endometritis - Mark A. Turrentine; Tracey A. Banks (Hindawi Limited, 1996)
Objective: We sought to determine if changing the surgeon's gloves after delivery of the infant and prior to manual placental removal decreases the incidence of postcesarean endometritis.